Evaluasi Penerapan Digital Marketing Sebagai Solusi Peningkatan Penjualan Umkm “Sarijan Coffee Malang” Di Masa Pandemi Covid-19 - Nafi`atuz Zahroh; N. Rachma; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study analyzed qualitatively the evaluation of the application of digital marketing as a solution to increase sales of Sarijan Cofee Malang MSME during the covid 19 pandemic. The data collection methods used were interviews and documentation. Based on the results of research and discussion regarding the use of social media whatsApp, Instagram, facebook and tiktok as well as the shopee marketplace well. The use of Sarijan Coffee UMKM Digital Marketing such as the use of Instagram and Facebook social media makes it easier to share information, becomes an efficient promotional media, becomes a medium for interaction with consumers and can expand reaching consumers. The use of chat media makes it easier for consumers to communicate with sellers, to communicate products, promote and order products and increase loyal customers. The use of the shopee marketplace makes it easier to reach consumers, makes it easier for consumers to see products, communicate, and make it easier for consumers to get our products by ordering online and not having to leave the house. At this time, many consumers prefer to use the Shopee marketplace in their transactions. By selling digitally, it really helps increase revenue which is also automatically accompanied by an increase in sales as well. This is proof that digital marketing has a big influence in increasing sales in the Sarijan Coffee Malang MSME business. Keywords: Digital Marketing, Sales Increase, Instagram, Facebook, Tiktok, WhatsApp, Marketplace.